Spent coffee ground properties and application in bioenergy and bioproducts - Brienzo, Michel [UNESP]; García-Aparicio, María; Görgens, Johann (My University, 2016)
Coffee is one of the most popular beverages (almost 9 million tons of coffee was consumed in 2014) and the second largest commodity traded worldwide. Coffee beans have long been used for human consumption, in the last centuries, producing coffee brews and instant coffee. About 50% of the coffee produced is directed for the production of soluble coffee generating spent coffee grounds (SCG) as a byproduct that is rich in carbohydrates, protein, lipids and bioactive molecules. SCG has found application as compost (soil conditioner), animal feed (poultry and ruminants), mushroom production, a substrate for fermentation (enzymes) and energy (biogas, liquid biofuel and bioelectricity). SCG composition and structure depends on the coffee beans used in the coffee production, as well as the industrial extraction process. The instant coffee manufacturing uses several hot water extraction steps with different temperature and its severity influences in the soluble solids extraction from the roasted beans and the characteristics of the generated SCG. The industrial process impacts on the amount of SCG generated and soluble compounds extraction, in average 4 kg of wet SCG per kilogram of instant coffee produced. Moreover, the structure of the remained polysaccharides in SCG, cellulose, galactomannan and arabinogalactan, can be more recalcitrant to further use. The SCG still contain extractable compounds (flavor and oil) in a lignocellulosic matrix formed by cellulose, hemicelluloses and lignin. These structural compounds are organized in the cell wall as a recalcitrant structure to the biological conversion process. Moreover, SCG is resistant to degradation and may need a pretreatment to make the material suitable for biotechnological conversion. The pretreatment disrupts the cellulose-hemicellulose-lignin structure, changing its properties and allowing a complex of cellulolytic and hemicellulolytic enzymes breaking down polysaccharides into fermentable sugars. The factors responsible for SCG recalcitrance is related to its chemical composition, structural and physicochemical properties that influence the pretreatment response end requires a complex pool of enzymes to its hydrolysis. This review will focus on discuss the recalcitrance properties of the SCG, based on its composition and structural organization, and the complex enzyme necessary for its conversion, highlighting its impact on biotechnology and bioenergy process.
Keywords: Biodiesel; Bioenergy; Cellulosic ethanol; Enzymatic hydrolysis; Polysaccharides; Recalcitrance; Spent coffee ground